PRINCIPLES OF CONSTRUCTION OF UNIVERSAL MEASURING ANTENNA - Ільницький, Л. Я.; Щербина, О. А.; Мартиновченко, К. В. (Science-based technologies, 2014)
Principle of construction of universal five-element measuring antenna is considered, which can be used in mobile radio monitoring stations. The main theoretical principles and ratios are present which can be used when designing the antenna system. There is the substantiation of antenna design, which consists of five linear elements (dipole antennas). The uniqueness of the measurement of the meridian and azimuthal angles of arrival of the waves by the investigated antenna system is proved. The antenna system, which consists of five active monopoles, uniquely takes the bearings of the location of the radiation source and measures the electromagnetic field. At the same time the antenna system does not require orientation in the space according to the direction of incidence of the electromagnetic wave. This significantly increases the speed of measuring device and the measurement accuracy increases. Use of the active monopoles in the antenna system gives the opportunity to work in a wide frequency band, because the effective length of each vibrator not depends on the frequency.